Short-term exposure to ambient air pollution increased in-hospital non-ST-elevation myocardial infarction mortality risk, but not ST-elevation myocardial infarction: case-crossover based evidence from Beijing, China - Zhao, Yakun; Chen, Yuxiong; Liu, Yanbo; Tang, Siqi; Han, Yitao; Zhuang, Yuansong; Fu, Jia; Chang, Zhen’ge; Zhao, Xinlong; Lei, Jinyan; Fan, Zhongjie (Frontiers in Public Health, 2025)
BackgroundPrevious studies have shown that air pollution affects the incidence of ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI) differently. However, limited studies have examined the impact of air pollution on the mortality of these acute myocardial infarction (AMI) subtypes.MethodsUsing AMI hospitalization data from Beijing (2013–2019), we applied a time-stratified case-crossover design with conditional Poisson regression models to evaluate associations between short-term exposure to six pollutants (PM2.5, PM10, SO2, NO2, CO, and O3) and daily in-hospital mortality for overall AMI, STEMI, and NSTEMI. Subgroup analyses based on demographics, comorbidities, and coronary artery disease (CAD) history were conducted to identify vulnerable populations. Additionally, a retrospective case–control analysis with multivariable logistic regression involved all AMI admission cases, was conducted to explore whether the association between air pollution exposure and in-hospital AMI mortality is independent of other mortality risk factors.ResultsDuring the study period, there were 149,632 AMI admissions, with 10,983 in-hospital deaths (4,361 STEMI and 4,299 NSTEMI). Elevated levels of PM2.5, PM10, SO2, NO2, and CO on admission day were significantly associated with increased in-hospital mortality for overall AMI and NSTEMI, but not for STEMI. The effect of pollutants on NSTEMI mortality was greater in patients with old myocardial infarction (OMI) or percutaneous coronary intervention/coronary artery bypass grafting (PCI/CABG) history. In case–control analysis with multivariable logistic regression, increased pollutants concentration remained significantly associated with in-hospital NSTEMI mortality after adjusting for other mortality risk factors.ConclusionShort-term exposure to PM2.5, PM10, SO2, NO2, and CO increases the risk of in-hospital AMI mortality, particularly for NSTEMI. Individuals with CAD history require more protective measures due to the vulnerability to air pollution.